(untitled) (Research, Society and Development, 2022)
Studies on the importance of root biomass and the effects that changes in vegetation coverage cause on carbon amount and stock are scarce, especially in the cerrado biome. Taking into account the scarcity of information about root biomass estimates, this work aimed to quantify root biomass under different land uses and native cerrado in Tocantins, Brazil. The research was conducted in different land uses: agriculture, pasture, eucalyptus and control with native cerrado forest. Six trenches with dimensions of 70 x 70 cm were opened and root biomass was collected at depths of 0-10, 10-20, 20-30, 30-40 and 40-50 cm. With the aid of a sieve, root biomass was collected and separated into fine and coarse roots. The amounts of fine and coarse root biomass showed the highest mean values of 7.7 and 12.9 g, respectively, in the eucalyptus area. Root biomass stocks were higher in the eucalyptus area, with maximum values above 3.68 Mg ha-1. Root biomass amounts and stocks were greater in eucalyptus areas, since forest areas, whether planted or native, manage to keep the environment in balance due to their long-term cycles, greater stability and low degree of disturbance.